Correction: Corrigendum: Elimination of HIV-1 Genomes from Human T-lymphoid Cells by CRISPR/Cas9 Gene Editing - Kaminski, Rafal; Chen, Yilan; Fischer, Tracy; Tedaldi, Ellen; Napoli, Alessandro; Zhang, Yonggang; Karn, Jonathan; Hu, Wenhui; Khalili, Kamel (Scientific reports, 2016)
Scientific Reports 6: Article number: 22555; published online: 04 March 2016; updated: 07 July 2016 The Competing financial interests statement in this Article should read: “KK, WH, RK, and YZ are named inventors on patents that cover the viral gene editing technology that is the subject of this published journal article.